Why Do They Stay? Analyzing Organizational Commitment of Non-Regular Participants in BEM FKIK Universitas Jambi - Amanda Eka Putri; Beny Rahim (Universitas Mercu Buana, 2026)
Student participation in organizational programs without formal membership raises an important question: why do participants remain engaged until completion? Such sustained involvement reflects organizational commitment, which can be understood through Meyer and Allen’s three-component model: affective, normative, and continuance commitment. This study aims to analyze the organizational commitment profiles of non-regular participants in the School of BEM FKIK Universitas Jambi 2025. This study employed a quantitative descriptive approach with a cross-sectional design. Using total sampling, 76 students from Nursing, Psychology, Public Health, and Pharmacy who completed the program were included. Data were collected using the Organizational Commitment Questionnaire (OCQ) based on Meyer and Allen’s (1991) framework and analyzed using descriptive statistics to identify dominant commitment types. The results showed that 33 participants (43.4%) demonstrated dominant affective commitment, followed by normative (34.2%), continuance (2.6%), and mixed profiles (19.7%). These findings indicate that sustained participation is primarily driven by emotional attachment, personal interest, and alignment with organizational values. Theoretically, this study extends the application of the three-component model to non-formal organizational contexts. Practically, and from a managerial perspective, understanding these commitment patterns enables BEM to design engagement strategies that strengthen emotional bonds, improve participant retention, and ensure organizational sustainability and leadership continuity.